Growth and stand dynamics of Red maple-dominated forests in the Upper Great Lakes Region, USA - Pszwaro, Justin Luke (My University, 2015)
Red maple (Acer rubrum L.) was historically a common but not abundant tree species in North American temperate forests. Over the last several decades it has increased in abundance on upland sites throughout its range and today is perhaps the single most abundant tree species in eastern North America. Climate change and associated impacts on forest dynamics are expected to increase red maple relative importance in the Upper Lake States and New England. However, red maple lacks commercial importance and has thus received little attention in growth studies and little is known of the dynamics of red maple-dominated stands. The objectives of this thesis were to 1) quantify the effects of stocking level and stand age on overall patterns of red maple stand productivity, 2) evaluate how these relationships vary across different geographic locations and climatic conditions, and 3) describe the composition dynamics of pure red maple-dominated forest stands.
University of Minnesota M.S. thesis. February 2015. Major: Natural Resources Science and Management. Advisor: Anthony W. D’Amato, Ph.D. 1 computer file (PDF); xiii, 89 pages, appendices p. 71-89.
Keywords: Climate; Growth modeling; Red maple; Stand dynamics; Natural resources science and management